Making Family-Centered Care for Adults in the ICU a Reality - Schwartz, Ann C.; Dunn, Sarah E.; Simon, Hannah F. M.; Velasquez, Alvaro; Garner, David; Tran, Duc Quang; Kaslow, Nadine J. (Frontiers in Psychiatry, 2022)
Despite the value of family-centered care (FCC) in intensive care units (ICUs), this approach is rarely a reality in this context. This article aims to increase the likelihood that ICU-based care incorporates best practices for FCC. Consistent with this goal, this article begins by overviewing FCC and its merits and challenges in ICUs. It then offers a systemic framework for conceptualizing FCC in this challenging environment, as such a model can help guide the implementation of this invaluable approach. This systemic framework combined with previous guidelines for FCC in the ICU are used to inform the series of recommended best practices for FCC in the ICU that balance the needs and realities of patients, families, and the interprofessional healthcare team. These best practices reflect an integration of the existing literature and previously published guidelines as well as our experiences as healthcare providers, family members, and patients. We encourage healthcare leaders and interprofessional ICU healthcare teams to adopt these best practices and modify them for the specific healthcare needs of the patients they serve and their families.